Opportunities for Guided Multichannel Non-invasive Transcranial Current Stimulation in Poststroke Rehabilitation - Otal, Begonya; Dutta, Anirban; Foerster, Águida; Ripolles, Oscar; Kuceyeski, Amy; Miranda, Pedro C.; Edwards, Dylan J.; Ilić, Tihomir V.; Nitsche, Michael A.; Ruffini, Giulio (Frontiers in Neurology, 2016)
Stroke is a leading cause of serious long-term disability worldwide. Functional outcome depends on stroke location, severity and early intervention. Conventional rehabilitation strategies have limited effectiveness, and new treatments still fail to keep pace, in part due to a lack of understanding of the different stages in brain recovery and the vast heterogeneity in the post-stroke population. Innovative methodologies for restorative neurorehabilitation are required to reduce long-term disability and socioeconomic burden. Neuroplasticity is involved in post-stroke functional disturbances, and also during rehabilitation. Tackling post-stroke neuroplasticity by non-invasive brain stimulation is regarded as promising, but efficacy might be limited because of rather uniform application across patients despite individual heterogeneity of lesions, symptoms and other factors. Transcranial direct current stimulation (tDCS) induces and modulates neuroplasticity, and has been shown to be able to improve motor and cognitive functions. tDCS is suited to improve post-stroke rehabilitation outcomes, but effect sizes are often moderate and suffer from variability. Indeed, the location, extent and pattern of functional network connectivity disruption should be considered when determining the optimal location sites for tDCS therapies. Here, we present potential opportunities for neuroimaging-guided tDCS-based rehabilitation strategies after stroke that could be personalized. We introduce innovative multimodal intervention protocols based on multichannel tDCS montages, neuroimaging methods and real-time closed-loop systems to guide therapy. This might help to overcome current treatment limitations in post-stroke rehabilitation and increase our general understanding of adaptive neuroplasticity leading to neural reorganization after stroke.